On Strongly $θ(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concept of strongly $θ(τ_1,τ_2)$-continuous functions. Furthermore, some characterizations and several properties concerning strongly $θ(τ_1,τ_2)$-continuous functions are considered.
Keywords: $(τ_1,τ_2)θ$-open set; strongly $θ(τ_1,τ_2)$-continuous function